In silico Study of New Five-Membered Heterocyclic Derivatives Bearing (1,3,4-oxadiazole and 1,3,4-thiadiazole) As Promising Cyclooxygenase Inhibitors (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2024)
A novel series of pyrazole, oxadiazole and thiadiazole bearing Nabumetone moiety were designed, synthesized, and evaluated for their anti-inflammatory activity against cyclooxygenase enzyme 2, after Insilico assay (by molecular docking study) a best set has been synthesized and characterized. After prediction of their activity by molecular docking study using Cambridge Crystallographic Data Base software tool (GOLD), We tested them in real in vivo as anti-inflammatory agents using egg white procedure. Due to their hydrogen bonding interaction with crucial amino acids in COX-2 isozymes Arg120, Tyr355, and Ser530, all tested compounds in molecular docking demonstrated significant activities compared with diclofenac, naproxen, and 6MNA as reference drugs. The data obtained from docking studies were highly correlated with that obtained from the in vivo assay in which compounds 3c, 6c, and 7c showed the best docking PLP fitness which were 91.35, 89.66, and 92.09 respectively with COX-2. Other compounds 2c, 4c, 5c, 6a, 6b, showed a PLP fitness above 80. The aim of this investigation was to produce novel NSAIDs, based on Nabumetone, that exhibit little or no gastro-toxicity and higher selectivity. This research offered helpful direction for the identification of novel pyrazole and thiadiazole anti-inflammatory compounds.